STRUGGLE AGAINST TYRANICAL REGIME IN TOLSTOYâS HADJI MURAD (1904): MARXIST CRITICISM - Fauzi, Arifah Nurul (JoLLIET, 2016)
The major problem of this study is describing the struggle to fight againsttyrannical regime in Chechnya reflected in Leo Tolstoyâs Hadji Murad. Theobjective of this study is to analyze the novel based on Marxist approach.The writer employs qualitative method. The object of the study is LeoTolstoyâs novel Hadji Murad published in 1904. The writer uses two datasources: primary and secondary. The primary data source is the text of HadjiMurad by Leo Tolstoy, published by Pensylvania State University and thesecondary data source are references and materials related to the study whichare taken from books or internet. The technique of data collection isdocumentation and the technique of data analysis is descriptive analysis.Based on the analysis, the writer gets two conclusions. First, through HadjiMurad novel, Tolstoy delivers a message that hero is a matter of perspective.Second, the Hadji Murad novel reflects the social realities of the ChechenMuslims in the struggling against the Russian tyrannical regime that reflectTolstoyâs support to the proletariat class.Key words: Hadji Murad, Marxist, regime, struggle, tyranny, Tolstoy